PREMILINARY ESTIMATION RESULTS OF IMPACT OF CLIMATE CHANGE ON MARINE FISHERIES IN VIETNAM BY USING PRODUCTION FUNCTION - Thanh, Nguyễn Ngọc; Thành, Nguyễn Viết; Toán, Dư Văn; Hùng, Ngô Thọ (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents an premilinary estimation of climate change impacts on marine fishery in Vietnam. An augmented production function is used in the present study to model the effects of climate change on fishery outputs, in order to determine the impact of climate change on marine fisheries in Vietnam. The data by time series of catch, fishing effort, labour, average temperature and annual number of typhoons from 1976 to 2010 have been collected and analyzed. The preliminary results show that the annual average rainfall in coastal areas has negatively effected to Vietnam’s catching production. However, the impacts of increasing rainfall on catching production are relatively smaller than those of other examined factors such as fleet capacity and labour.